PENENTUAN BESAR ENERGI LISTRIK AKI DENGAN MEMVARIASIKAN JUMLAH AIR SULING (H2O) DAN ASAM SULFAT (H 2SO4 ) - Romadona '; Maksi Ginting; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been conducted to determine electrical energy  of accu   with variation of volume  of distilled water and sulfuric acid. In this study, an  electrolyte solution  of 400 ml  was prepared  for each accu  consisting of a mixture of distilled water and sulfuric acid with different compositions.  Measurements  of each sample  were  carried out at  the interval time of  15 minutes for 2 hours. The results showed that the  amount of  energy produced by  accu  with a standard electrolyte solution  expenses  factory for 2 hours  was 114.14   kilojoules. The amounts  of  energy  obtained  from the  variation of  the mixture composition  of the electrolyte solution  ratio  were  154.23  kilojoules, 156.73  kilojoules, and  141.61 kilojoules, respectively for a mixture of distilled water and sulfuric acid witha composition ratio  of  64% :  36%, 60% :  40%,  and  70% : 30%,  where  as  for a mixed electrolyte solution with  aquabides and  sulfuric acid,  resulted the energy of  164.18 kilojoules, 157.37 kilojoules, and  148.52 kilojoules, respectively for the mixture ratio of 64%  : 36%, 60%  : 40%,  and  70%  : 30%.  Conclusion,  the  largest energy   produced  was obtained  by the  accu with  electrolyte solution  containing a  mixture of  sulfuric  acid  and  aquabides with the composition ratio of 64% : 36%.